The Courtships of Lancaster County: Courting Cate - Book 1 - Gould, Leslie, 1962- (Minneapolis, Minn. : Bethany House, 2012)
Cate Miller has scared off every suitor. Pete Troyer has never failed at anything. Could he be the one to finally tame the fiery Cate?
Keywords: Amish -- Fiction; Lancaster County (Pa.) -- Fiction; Single women -- Fiction; Farmers -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Love stories